Reimagining Signature Pedagogies through Digital Prototypes: Inclusive Disciplinary learning in Geography and Mathematics - Macchia, Vanessa; Torri, Stefania (ITALIAN JOURNAL OF EDUCATIONAL RESEARCH, 2025)
The purpose of this article is to explore how digital innovation can improve subject teaching in Geography and Mathematics in the primary and lower secondary school through the development of inclusive and interactive prototypes. The study adopts the principle of signature pedagogies to analyse four digital learning units developed within the Erasmus+ XXX project. These prototypes, designed for primary and lower secondary education, incorporate multimodal resources, accessibility features and differentiated learning paths to address the diverse needs of learners. The analysis follows a qualitative approach and is guided by criteria focused on the authenticity of disciplinary practices, the usability of digital tools and equitable access to content. Findings suggest that technology, when thoughtfully integrated, can reinforce subject- specific learning while ensuring equitable access for all students.